ANALISIS PENANGGULANGAN MASALAH SHALE PADA TRAYEK 8 ½" MENGGUNAKAN KCL - POLYMER POLYAMINE PADA SUMUR MKLS - Mukhlis Farhan Rivani; Nijusiho Manik; Amiruddin Amiruddin; Esterina Natalia Paindan (PETROGAS: Journal of Energy and Technology, 2026)
Shale formations in the 8 ½” section of MKLS Well in East Kalimantan present drilling challenges due to their reactive nature at high temperatures up to 250°F. The interaction between water-based mud and clay minerals can cause swelling, sloughing, and bit balling, which increase Non-Productive Time (NPT) and operational risks. This study aims to evaluate the effectiveness of a High Performance Water-Based Mud (HPWBM) system based on KCl–Polymer Polyamine in mitigating these risks. Testing included mud property evaluation, Linear Swelling Meter (LSM), Erosion Test, and Accretion Test using shale cuttings from MKLS Well. Results show a mud density of 1.36 g/cc, plastic viscosity of 15 cP, yield point of 25 lb/100 ft², filtrate loss of 4.8 mL/30 minutes, and pH of 9.40. Swelling of 3.5% (72 hours), erosion of 2.6%, and accretion of 1.45% indicate good inhibition, reducing wellbore instability, shale sloughing, tight hole, pack-off, and bit balling.